The Role Of Civic Education Teachers In Improving Students’ Moral Values In Elementary Schools - Rizky Rahayu; Vega Bintang Rizky; Nur Hidayat (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
This study aims to find out how the influence of civics education teachers has on student morale in elementary schools. This type of research is descriptive qualitative. Collecting data using interview and observation techniques. The subjects of this study were two teachers, school principals and students of citizenship education who were identified using a purposive sampling technique. The collected data were analyzed using descriptive analysis. The results of this study indicate that: At SDN Nanggulan the role of educators is through several indicators (1) educators as designers, (2) educators as initiators, (3) educators as motivators, (4) educators as observers, (5) educators as anti-adversators, (6) educators as models, (7) educators as evaluators, (8) educators as friends who explore with students, and (9) educators as promoters so that students become true learners. This is to ensure that civics teachers can help students develop free moral values to help students do it at school. While the supporting factors for the successful formation of moral values in students are infrastructure, regulations and teachers.